The efficacy of laparoscopic presacral neurectomy in dysmenorrhea: Is it related to the amount of excised neural tissue? - Api, Murat; Boza, Ayşen; Ceyhan, Mehmet; Kaygusuz, Ecmel; Yavuz, Hülya; Api, Oluş (My University, 2017)
Objective: To assess the correlation between the number of excised neural fibers and degree of pain relief following laparoscopic presacral neurectomy (LPSN).Materials and Methods: In this before and after study, 20 patients with severe midline dysmenorrhea [Visual Analogue Scale (VAS) >80 mm] unresponsive to medical therapy were consecutively enrolled. All patients underwent LPSN. The superior hypogastric plexus was excised and sent for histologic confirmation. Two pathologists counted the number of neural fibers in the surgically removed tissue. VAS was used for pain assessment before and 2nd, 3rd, 6th, and 12th months after the operations.Results: Out of the initial 20 patients undergoing LPSN, eight were excluded from the final analysis due to intraoperative diagnosis of endometriosis; therefore, the remaining 12 patients were evaluated. The pain scores significantly decreased at each follow-up visit compared with the preoperative period (p=0.002). The pathologists, who were blinded, reported the median (minimum-maximum) neural fiber count as 46 and 47 . No significant correlation was demonstrated between the number of excised neural fibers and the amount of pain relief following LPSN. Conclusion: LPSN is an effective surgical procedure to control primary dysmenorrhea. Our preliminary results revealed that the degree of pain relief in cases of severe midline dysmenorrhea was not related to the amount of excised neural tissue in LPSN.

Amaç: Laparoskopik presakral nörektomi (LPSN) sonrası ağrı miktarındaki azalma ile çıkarılan nöral doku miktarı arasındaki korelasyonun değerlendirilmesidir. Gereç ve Yöntemler: Medikal tedaviye dirençli, şiddetli orta hat dismenoresi olan [Vizüel Analog Skoru; (VAS) >80 mm] ve LPSN yapılmaya karar verilen 20 ardışık hasta çalışmaya dahil edildi. Operasyonda eksize edilen süperior hipogastrik pleksus histolojik konfirmasyon için patolojiye gönderildi. Cerrahi olarak çıkarılan nöral fibriller iki patolog tarafından ayrı ayrı sayıldı. Operasyon öncesi ve operasyon sonrası 2., 3., 6. ve 12. aylarda hastaların ağrısı VAS ile değerlendirildi.Bulgular: LPSN yapılan 20 hastanın 8'i intraoperatif endometriozis tanısı aldığı için analizden çıkarıldı, geriye kalan 12 hasta değerlendirildi. Ağrı skorlarının postoperatif dönemdeki her bir vizitte preoperatif dönem ile kıyaslandığında anlamlı oranda düştüğü izlendi (p=0,002). İki patolog tarafından rapor edilen medyan (minimum-maksimum) nöral fibril sayısı 46 ve 47 idi. Eksize edilen nöral fibril sayısı ile LPSN sonrasındaki ağrı azalması arasında anlamlı bir korelasyon bulunmadı. Sonuç: LPSN primer dismoreyi tedavi etmede etkili bir cerrahi prosedürdür. Elde edilen ön sonuçlara göre ciddi orta hat dismorede LPSN ile eksize edilen nöral doku miktarı ile ağrı iyileşmesi arasında herhangi bir ilişki yoktur.
Laparoskopik presakral nörektominin etkinliği çıkartılan nöral doku miktarı ile ilişkili midir?
Keywords: Dismenore; Dysmenorrhea; Nerve Fiber; Presacral Neurectomy; Laparoscopy; Sinir Lifi; Presakral Nörektomi; Laparoskopi